Electrochemical synthesis of hydroxy-thioxo-imidazole carboxylates: an experimental and theoretical study. (3rd March 2020) - Sbei, Najoua; Said, Ridha Ben; Rahali, Seyfeddine; Beya, Haouas; Al-Ayed, Abdullah S.; Al Mogren, Muneerah Mogren; Benkhoud, Mohamed Lamin; Seydou, Mahamadou
ABSTRACT: We report here the facile synthesis of a new series of hydroxy-thioxo-imidazole carboxylates in good yields using the cyanomethyl anion as an electrogenerated base which is formed when dry acetonitrile is electrolyzed at constant current, followed by addition of different thioureas and diazirine-3, 3-dicarboxylate. The mechanism of the reaction, NMR shifts and IR are discussed and compared to density functional theory calculations. GRAPHICAL ABSTRACT: